2021
DOI: 10.3390/su13179530
|View full text |Cite
|
Sign up to set email alerts
|

Sportive Fashion Trend Reports: A Hybrid Style Analysis Based on Deep Learning Techniques

Abstract: This study aimed to use quantitative methods and deep learning techniques to report sportive fashion trends. We collected sportive fashion images from fashion collections of the past decades and utilized the multi-label graph convolutional network (ML-GCN) model to detect and explore hybrid styles. Based on the literature review, we proposed a theoretical framework to investigate sportive fashion trends. The ML-GCN was designed to classify five style categories, “street,” “retro,” “sexy,” “modern,” and “sporty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…It belongs to an important research direction in machine learning under artificial intelligence, and is also an extension of representation learning theory. Deep learning differs from other learning methods and general system building in that it increases the depth of the hidden layer and extracts more abstract feature information from the hidden layer of the previous layer, effectively avoiding the interference factors brought about between different features [6][7][8]. Interaction between measurements is an important issue in poor data recognition for state estimation, and determining the interaction between measurements directly from the network topology may result in areas that are too large or too small, missing measurements that may interact with each other or covering non-interactive measurements.…”
Section: Deep Learning-based Assessment Of the Operational Status Of ...mentioning
confidence: 99%
“…It belongs to an important research direction in machine learning under artificial intelligence, and is also an extension of representation learning theory. Deep learning differs from other learning methods and general system building in that it increases the depth of the hidden layer and extracts more abstract feature information from the hidden layer of the previous layer, effectively avoiding the interference factors brought about between different features [6][7][8]. Interaction between measurements is an important issue in poor data recognition for state estimation, and determining the interaction between measurements directly from the network topology may result in areas that are too large or too small, missing measurements that may interact with each other or covering non-interactive measurements.…”
Section: Deep Learning-based Assessment Of the Operational Status Of ...mentioning
confidence: 99%
“…DL has enabled AI systems to achieve significant performance improvements in many important problems such as CV, ASR, and NLP. It has become the key to the current breakthrough of AI [14]. Fig.…”
Section: A Ai and Nnsmentioning
confidence: 99%
“…The patients were treated with Bushen-Liyan Decoction and their symptoms were evaluated. The results showed that the total effective rate was 83.33% [4][5][6]. Qiyan Decoction can effectively treat patients with dysphagia after stroke with internal obstruction of blood stasis.…”
Section: Introductionmentioning
confidence: 99%